Spectral distances explain higher variation in plant beta - diversity than spatial autocorrelation :Powerpoint - Groen, T.A. (University of Twente, 2020)
This lecture integrated assessment: Lake Naivasha; Changes in biodiversity of fringe; Lake level fluctuations; Would like to “reconstruct” past‐diversity around the fringe.